CHANGES IN THE KIDNEYS IN PATIENTS WITH A PERIOD OF REHABILITATION AFTER THE DISEASE COVID-19 - Botir Xamzayevich, Yo`ldoshev (European Journal of Life Safety and Stability (2660-9630), 2021)
Although COVID-19 infection is a disease that is mainly accompanied by respiratory tract lesions, a few cases of the disease occurring at different levels (mild, moderate, severe), scientists have been telling. Against the background of post-covid syndrome, which develops after the disease at moderate to severe levels of Covid 19, violations of kidney functional activity and its dependence on the body’s auto-immune processes are being studied until now